Cover Picture: Label‐Free Direct Electrical Detection of a Histidine‐Rich Protein with Sub‐Femtomolar Sensitivity using an Organic Field‐Effect Transistor (ChemistryOpen 4/2017). Issue 4 (21st July 2017) - Minamiki, Tsukuru; Sasaki, Yui; Tokito, Shizuo; Minami, Tsuyoshi
Abstract : The Front Cover picture shows an electrical bioassay for the label‐free and highly‐sensitive detection of a histidine‐rich protein (serum albumin) using an organic filed‐effect transistor (an OFET) modified with a Ni II ‐trinitriloacetic acid monolayer (Ni II ‐nta). More information can be found in the Communication by T. Minamiki et al. onpage 472 in Issue 6, 2017 (DOI:10.1002/open.201700070 ).